Non-specific interstitial pneumonia as pulmonary involvement of systemic sclerosis. Issue 3 (1st March 2001) - Fujita, J; Yoshinouchi, T; Ohtsuki, Y; Tokuda, M; Yang, Y; Yamadori, I; Bandoh, S; Ishida, T; Takahara, J; Ueda, R
Abstract : The pathological features of lung disease in nine patients with systemic sclerosis (SSc) were evaluated. The patients comprised one man and eight women, with a median age of 58 years. SSc was diagnosed according to the criteria of the American Rheumatism Association. In all patients, high resolution computed radiographic scanning of the lungs (HRCT) was performed, and apparent honeycomb formation was seen in four patients. Pathologically, four patients were diagnosed with usual interstitial pneumonia (UIP), three with non-specific interstitial pneumonia (NSIP) group II, one NSIP group II–III, and one NSIP group II with diffuse alveolar damage. HRCT showed no apparent honeycomb formations in patients diagnosed with NSIP. This is the first report describing NSIP as a pulmonary complication of SSc.